A Prospect of the Palace of Lichtenstein in the Suburbs of Rossau, on the side of the Danube - Bishop (engraver):::Creator::::::::::::; Van Ert, I.E.F. (artist):::Contributor:::::::::::: (London; Printed for John Bowles at the Black Horse in Cornhill; United Kingdom)
Color engraving of the Liechtenstein Palace in the Rossau suburbs of Vienna